Nutrient addition drives declines in grassland species richness primarily via enhanced species loss - Muehleisen, Andrew (Dryad, 2022)
Declines in grassland diversity in response to nutrient addition are a
general consequence of global change. This decline in species richness may
be driven by multiple underlying processes operating at different
timescales. Nutrient addition can reduce diversity by enhancing the rate
of local extinction via competitive exclusion, or by reducing the rate of
colonization by constraining the pool of species able to colonize under
new conditions. Partitioning net change into extinction and colonization
rates will better delineate the long-term effect of global change in
grasslands. We synthesized changes in richness in response to experimental
fertilization with nitrogen, phosphorus, and potassium with micronutrients
across 30 grasslands. We quantified changes in local richness,
colonization, and extinction over 8-10 years of nutrient addition, and
compared these rates against control conditions to isolate the effect of
nutrient addition from background dynamics. Total richness at steady state
in the control plots was the sum of equal, relatively high rates of local
colonization and extinction. On aggregate, 30-35% of initial species were
lost and the same proportion of new species was gained at least once over
a decade. Absolute turnover increased with site-level richness but was
proportionately greater at lower-richness sites relative to starting
richness. Loss of total richness with nutrient addition, especially N in
combination with P or K, was driven by enhanced rates of extinction with a
smaller contribution from reduced colonization. Enhanced extinction and
reduced colonization were disproportionately among native species,
perennials, and forbs. Reduced colonization plateaued after the first few
(< 5) years after nutrient addition, while enhanced extinction
continued throughout the first decade. Synthesis: Our results indicate a
high rate of colonizations and extinctions underlying the richness of
ambient communities, and that nutrient enhancement drives overall declines
in diversity primarily by the exclusion of previously established species.
Moreover, enhanced extinction continues over long time scales, suggesting
continuous, long-term community responses and a need for long-term study
to fully realize the extinction impact of increased nutrients on grassland
composition.
The Nutrient Network (NutNet) is a globally distributed experiment
replicated across short-statured, primarily herbaceous ecosystems
(hereafter called grasslands) on six continents. Most sites with
experimental treatments contain three replicated treatment blocks (21 of
30 sites; range 1 - 6 blocks per site). Within each block, eight different
nutrient addition treatments are applied to 5 x 5 m plots. Thus, most
sites have a total of 24 experimental units (3 blocks x 8 nutrient
treatments; Borer, Harpole, et al., 2014). These nutrient addition
treatments represent the factorial combinations of nitrogen (N),
phosphorus (P), and potassium and micronutrients (K+), plus a control.
Nutrient addition rates are: 10 g N m-2 yr-1 as timed-release urea, 10 g P
m-2 yr-1 as triple superphosphate, 10 g K m-2 yr-1 as potassium sulfate,
and 100 g m-2 of a micronutrient mix (6% Ca, 3% Mg, 12% S, 0.1% B, 1% Cu,
17% Fe, 2.5% Mn, 0.05% Mo, and 1% Zn). N, P, and K are applied annually,
while the micronutrient mix was applied only once at the start of the
study to prevent toxicity of largely immobile micronutrients. Treatments
are hereafter referred to shorthand by their nutrient components e.g.,
‘NK’ for Nitrogen + Potassium and micronutrients, ‘NPK’ for full nutrient
additions. All present species are identified in each 5 x 5 m plot every
year at the time of peak biomass, or twice annually in highly seasonal
sites. For the current study, we only selected sites with at least eight
years of treatment data (n = 30 sites) to capture longer-term dynamics in
species turnover, as well as control for otherwise uneven sample sizes at
disparate time intervals.
Keywords: Ecology; Grasslands; nutrient deposition; species richness; FOS: Biological sciences